Autotransplantation or replantation of cryopreserved teeth: a case series and literature review. Issue 1 (10th March 2013) - Yoshizawa, Michiko; Koyama, Takahiro; Izumi, Naoya; Niimi, Kanae; Ono, Yukiko; Ajima, Hisao; Funayama, Akinori; Mikami, Toshihiko; Kobayashi, Tadaharu; Ono, Kazuhiro; Takagi, Ritsuo; Saito, Chikara
Abstract Background The aim of this report was to evaluate the outcome of autotransplantation or replantation of cryopreserved teeth clinically and radiographically. Donor teeth were slowly frozen in a controlled‐rate freezer using 5% dimethylsulfoxide (DMSO) and 6% hydroxyethyl starch (HES) as protectants. Seven cryopreserved teeth, with duration of storage ranging from 4 to 36 months, were autotransplanted or replanted at Niigata University Medical and Dental Hospital. Endodontic treatment involving root canal debridement followed by interim root canal filling with calcium hydroxide was started 3 weeks after the operation and continued with replacement of the calcium hydroxide filling at 2‐week to 3‐month intervals. Three transplants showed periodontal regeneration clinically and radiographically, whereas replacement root resorption was observed in the remaining transplants. From the results, it can be concluded that cryopreserved tooth autotransplantation has potential for clinical use; however, the risk of replacement root resorption remains.